EFFECTIVENESS OF INTERVENTIONAL PROGRAM ON QUALITY OF LIFE OF PATIENTS WITH CHRONIC KIDNEY DISEASE RECEIVING HEMODIALYSIS - Ankaj; Prof. (Dr). Poonam Sharma (The Bioscan, 2026)
Chronic Kidney Disease (CKD) is an irreversible, progressive condition that significantly impairs the kidneys' ability to function effectively. At its terminal stage-End-Stage Renal Disease (ESRD) Patients often rely on renal replacement therapy, the most common of which is haemodialysis. While haemodialysis prolongs survival, it imposes a substantial burden on the patient's physical, psychological, social, economic, and spiritual well-being. In modern clinical care, success is no longer measured solely by disease-specific outcomes such as survival rates or laboratory results. Rather, Quality of Life (QoL) has emerged as an equally critical parameter in evaluating health interventions, especially in chronic conditions. Thus, understanding and improving the QoL of CKD patients undergoing haemodialysis is a moral, clinical, and public health imperative. This section explores in depth why such a study is urgently needed.